Ubrzavanje. - Fine Art Gallery, Banja Luka; Denegri, Jesa; Karalic, Sasa; Sandqvist, Tom (Banja Luka : Gallery of Fine Arts, 1998)
Bothén, Paul ; Carlos, Isac ; Czajor, Renata ; Denegri, Jesa ; Hausswolff, Carl Michael von ; Jongedijk, Wim ; Karalic, Sasa ; Mannheimer, Sara ; Radinkovic, Zeljko ; Reis, Gilberto ; Sanders, Sebastian J. ; Sandqvist, Tom ; Schulte, Tanja ; Stefanovic, Jelena
biografie
Ubrzavanje / Quickening, Fine Art Gallery, Banja Luka, 01.09.98 - 01.10.98
Engels
boek